2012
DOI: 10.1002/jsid.94
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis analysis in excimer‐laser‐annealed low‐temperature polycrystalline‐silicon thin‐film transistors

Abstract: To analyze the hysteresis phenomenon in p‐channel low‐temperature polycrystalline‐silicon thin‐film transistors (LTPS TFTs), the direct correlation between the hysteresis and the interface (Nit) and the grain‐boundary trap density (Ntrap) has been investigated. To fabricate LTPS TFTs with different electrical properties and trap types, the thickness of a‐Si was varied from 30 to 80 nm and crystallized by the excimer‐laser‐anneal (ELA) method. The interface trap density is extracted from the subthreshold slope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…[10] The hysteresis decreased when the film thickness decreased to 30 nm by reducing the surface protrusion and the interface defect density. [11] 550 o C-annealed TFTs showed decrease of hysteresis compared with 490 o C-annealed TFTs. Fourier transform infrared (FT-IR) spectroscopy indicated that a 550 o C-annealed SiO2 film had less Si-OH bonds than a 490 o C-annealed film.…”
Section: Introductionmentioning
confidence: 84%
“…[10] The hysteresis decreased when the film thickness decreased to 30 nm by reducing the surface protrusion and the interface defect density. [11] 550 o C-annealed TFTs showed decrease of hysteresis compared with 490 o C-annealed TFTs. Fourier transform infrared (FT-IR) spectroscopy indicated that a 550 o C-annealed SiO2 film had less Si-OH bonds than a 490 o C-annealed film.…”
Section: Introductionmentioning
confidence: 84%
“…Recoverable image sticking is one of most important specifications inspected for mobile display, which is strongly related to hysteresis phenomenon in LTPS TFTs resulting in a threshold-voltage (Vth) shift [3][4]. In general, the main mechanism of the hysteresis phenomenon in poly-Si TFTs are reported as a trapping and detrapping process of free carriers associated with the intra-grain trap, grain-boundary trap, and interface trap between the active layer and gate insulator [5]. The protrusion height of poly-Si will impact the number of grain boundary traps, which will impact the hysteresis performance of PMOS thin film transistor (TFT) [6].…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…The hysteresis of the p-channel LTPS TFT can be explained by hole trapping and de-trapping at the interface region of the channel. There have been numerous reports to explain and trials to reduce the hysteresis by surface plasma treatment, annealing, thin active, and heating the panel, the minimum hysteresis was reported to be around 0.1V for poly-Si channel TFTs [5][6][7][8][9]. However, the research work on recovery phenomenon of the image sticking is relatively lacking, which can be attributed to the relaxation of the TFT drain current.…”
Section: Introductionmentioning
confidence: 99%